The Influence of Clean and Healthy Living Behavior Education on Changes in Student Behavior - Deli Syaputri; Samuel Marganda Halomoan Manalu; Desy Ari Apsari; Riyanto Suprawihadi (Universitas Islam Negeri Sumatera Utara, Medan, 2023)
A Clean and Healthy Lifestyle is an action or behavior related to health that is carried out based on self-awareness so that the family and all its members are able to be independent in maintaining their own health and have a high desire to maintain their health. The aim of this research is to determine the effect of counseling about clean and healthy living behavior on changes in student behavior regarding knowledge, attitudes and actions in increasing awareness of the importance of health and clean and healthy lifestyles in the school and community environment. This type of research is quasi-experimental and the research design used is One-Group Pretest-Posttest. The sample selection was taken from grades 4 and 5, totaling 45 students attending the State Elementary School 104274 Pematang Kasih, Pantai Cermin District, Serdang Bedagai Regency. sampling using total sampling technique. The instrument used in this research was a questionnaire and the socialization process was carried out through lectures, presentation of power points and videos to attract children's attention. data analysis using paired t-test with the help of Statistical Program for Social Science (SPSS) software version 20. The research results show that there is an influence of providing counseling about clean and healthy living behavior on students' knowledge p-value=0.000, there is an influence of providing counseling about clean and healthy living behavior on students' attitudes p-value=0.000, and there is an influence of providing counseling about clean and healthy living behavior on students' actions p-value=0.000 at State Elementary School 104274 Pematang Kasih, Pantai Cermin District, Serdang Bedagai Regency.Keywords: Actions, Attitudes, Counseling, Clean and healthy living behavior, Knowledge